REST protects dopaminergic neurons from mitochondrial and α-synuclein oligomer pathology in an alpha synuclein overexpressing BAC-transgenic mouse model - Ryan, BJ; Bengoa-Vergniory, N; Williamson, M; Kirkiz, E; Roberts, R; Corda, G; Sloan, M; Saqlain, S; Cherubini, M; Poppinga, J; Bogtofte, H; Cioroch, M; et al. (Society for Neuroscience, 2021)
Alpha-synuclein pathology is associated with dopaminergic neuronal loss in the substantia nigra (SN) of Parkinson's patients. Working across human and mouse models, we investigated mechanisms by which the accumulation of soluble α-synuclein oligomers leads to neurodegeneration. Biochemical analysis of the midbrain of α-synuclein overexpressing BAC-transgenic male and female mice revealed age- and region-dependent mitochondrial dysfunction and accumulation of damaged proteins downstream of the RE1 Silencing Transcription Factor (REST). Vulnerable SN dopaminergic neurons displayed low REST levels compared to neighbouring protected SN GABAergic neurons, which correlated with the accumulation of α-synuclein oligomers and disrupted mitochondrial morphology. Consistent with a protective role, REST levels were reduced in patient iPSC-derived dopaminergic neurons carrying the SNCA-Triplication mutation, which accumulated α-synuclein oligomers and mitochondrial damage, and displayed REST target gene dysregulation. Furthermore, CRISPR-mediated REST knockout induced mitochondrial dysfunction and impaired mitophagy in vitro. Conversely, REST overexpression attenuated mitochondrial toxicity and mitochondrial morphology disruption through the transcription factor PGC-1α. Finally, decreased α-synuclein oligomer accumulation and mitochondrial dysfunction in mice correlated with nuclear REST and PGC-1α in protected SN GABAergic neurons, when compared to vulnerable dopaminergic neurons. Our findings show that increased levels of α-synuclein oligomers cause dopaminergic neuronal-specific dysfunction through mitochondrial toxicity, which can be attenuated by REST in an early model of Parkinsonian pathology. These findings highlight REST as a mediator of dopaminergic vulnerability in PD.SIGNIFICANCE STATEMENT:Understanding early Parkinsonian pathophysiology through studies of advanced pre-clinical models is fundamental to the translation of disease-modifying therapies. Here we show disease-relevant levels of α-synuclein expression in mice leads to accumulation of α-synuclein oligomers in the absence of overt aggregation, and mitochondrial dysfunction in dopaminergic neurons lacking the RE1 Silencing Transcription Factor (REST). Our findings identify the mechanism of action of REST and PGC-1α as mediators of dopaminergic vulnerability in α-synuclein BAC-transgenic mice and iPSC-derived dopaminergic cultures, highlighting their potential as therapeutic targets.